Integration of Technology Enriched Games with Classical Teaching Instruments for the Development of Technical Communication Competencies - Ioan Cristian Mustața; Ioana Mustața (Journal of ICT, Design, Engineering and Technological Science, 2020)
This way, the paper aims to identify a balanced mix of technology-enriched games and classical teaching instruments that is well-suited for the efficient development of technical communication competencies by students or trainees. The paper addresses the issue of developing technical communication competencies, analyzing the competencies involved in a structured way and then proposing some enriched technology games as innovative instruments to be used by teachers and trainers together with the classical teaching instruments. For this purpose, classical teaching instruments are analyzed to identify their strengths and weaknesses when used to develop technical communication competencies. Then innovative complementary instruments – in this case, technology-enriched games - are identified and configured to address exactly the weak point of classical instruments in a better way. The aim of these technology-enriched games is not to replace classical teaching instruments but to be integrated as complementary instruments alongside them. This approach is a novelty in the context of actual research. The findings could be implemented in all courses containing technical communication – a field that is future-oriented and has a high potential for development in the near future.